Acupuncture Treatment for Social Defeat Stress - Kawanokuchi, Jun; Takagi, Ken; Tanahashi, Nobuyuki; Yamamoto, Teruhisa; Nagaoka, Nobuyuki; Ishida, Torao; Ma, Ning (Frontiers in Behavioral Neuroscience, 2021)
Depression is a mood disorder characterized by disordered affect, thought, cognition, and behavior. Antidepressant therapy is often the primary treatment for depression. But antidepressants therapy is considered to may cause unwanted side effects and effects of therapy are slow. Therefore, some patients are seeking alternative treatment for depression such as acupuncture. However, there are many unclear points about the mechanism of the effect of acupuncture on depression. In recent years, we have reported that acupuncture improves the symptoms of rat model of mild depression using a water-immersion stress and mouse model of depression induced by forced swimming (FS). In this study, we examined the effect of acupuncture using social defeat stress (SDS)-induced depression mice that most closely resemble human symptoms. In this study, we investigated preventive and therapeutic effects of acupuncture as part of GV20 “Bai-Hui” and Ex-HN3 “Yintng” on depression induced by SDS. To examine the mechanism of preventive and therapeutic effect of acupuncture on depression, we examined the expression of neurotrophic factors in the brain of SDS mice. Two weeks of simultaneous acupuncture stimulation as part of GV20 and Ex-HN3 restored SDS-reduced BDNF, NT-3 and NT-4/5 expression, but not antidepressants. On the other hand, acupuncture stimulation suppressed NGF expression increased by SDS. These results suggest that treatment with acupuncture could be effective by correcting the imbalance in expressions of neurotrophic factors. Further, effects of acupuncture on expressions of neurotrophic factors appear so earlier than antidepressants, that it may be an excellent treatment for depression.